Sustainable Tourism Behaviour through Walking Tour: A Qualitative Study to Walking Tour Participants in Jakarta - Altamira, Melisa Bunga; Putri, Khairunnisa Devani Aqtus Permana (Journal of Indonesian Tourism and Policy Studies, 2025)
As urban tourism continues to rise, walking tours have emerged as a low-impact, environmentally friendly, and culturally immersive form of tourism. This study explores the relationship between walking tours and the development of sustainable tourism behaviour among participants in Jakarta, Indonesia. Using a qualitative research approach, this study elaborates the motivations, perceptions, and behavioural changes of individuals who have participated in walking tours across Jakarta’s historical and cultural sites. Data were collected through in-depth interviews and participant observations, focusing on themes such as environmental awareness, appreciation of local culture, and reduced dependency on motorized transport. The findings suggest that walking tours not only promote a deeper connection between tourists and their surroundings but also foster pro-environmental attitudes and responsible travel behaviour. Moreover, participants reported increased awareness of heritage preservation and community-based tourism values. This study also highlights the potential of walking tours as a strategic tool in encouraging sustainable tourism practices in urban settings. Recommendations are offered for tour operators, urban planners, and policymakers to integrate walking tours into broader sustainability frameworks within the tourism sector.